Can computer-guided surgery help orthodontics in miniscrew insertion and corticotomies? A narrative review - Guarnieri, Rosanna; Grenga, Camilla; Altieri, Federica; Rocchetti, Federica; Barbato, Ersilia; Cassetta, Michele (Frontiers in Oral Health, 2023)
Orthodontics has considerably increased the use of technology combined with surgery as a tool to improve dental movements in terms of predictability, acceleration of movement, and fewer side effects. To achieve these goals miniscrews and corticotomy were introduced. The digital workflow permits an increase in the accuracy of surgical and orthodontic setups. The tool that transfers the information is the CAD/CAM (Computer-Aided Design/ Computer-Aided Manufacturing) template. The aim of this review is to illustrate the use of computer-guided surgery in orthodontics regarding miniscrews and piezocision. The search strategy was a combination of Medical Subject Headings (Mesh) and free text words for PubMed. A total of 27 articles were included in this review: 16 concerned miniscrews and 11 concerned corticotomy. The current need for faster treatments, the improved systems of anchorage, and the evolution of imaging technologies require operators to be knowledgeable of the digital workflow. CAD/CAM templates allow greater precision and predictability of miniscrew insertion even if in the hands of less experienced clinicians and permit a better orientation and depth of the cortical incision. In conclusion, digital planning makes surgery faster and easier and allows for the identification and correction of any potential problem before the procedure.